2009
DOI: 10.1212/wnl.0b013e3181a4124e
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cortical thinning in the language variants of frontotemporal lobar degeneration

Abstract: The language variants of frontotemporal lobar degeneration have distinctive and significantly different patterns of cortical thinning. Increasing disease severity is associated with spread of cortical thinning and the pattern of spread is consistent with progression of clinical deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
194
1
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(229 citation statements)
references
References 43 publications
26
194
1
8
Order By: Relevance
“…We further investigated the reliability of focal atrophy across individual patients and found that 100% of individuals in both svPPA samples had one of their maximally atrophic points in the same temporopolar region. Beyond the anterior temporal cortex, patients with svPPA exhibit less prominent neurodegeneration in distributed cortical and subcortical regions (Mummery et al, 2000;Rosen et al, 2002;Gorno-Tempini et al, 2004;Brambati et al, 2009;Rohrer et al, 2009). As predicted, the focal atrophy point identified in our cortical thickness analysis was interconnected with a network of brain regions in healthy adults that closely resembled the distributed cortical atrophy pattern of svPPA patients, replicating previous findings .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We further investigated the reliability of focal atrophy across individual patients and found that 100% of individuals in both svPPA samples had one of their maximally atrophic points in the same temporopolar region. Beyond the anterior temporal cortex, patients with svPPA exhibit less prominent neurodegeneration in distributed cortical and subcortical regions (Mummery et al, 2000;Rosen et al, 2002;Gorno-Tempini et al, 2004;Brambati et al, 2009;Rohrer et al, 2009). As predicted, the focal atrophy point identified in our cortical thickness analysis was interconnected with a network of brain regions in healthy adults that closely resembled the distributed cortical atrophy pattern of svPPA patients, replicating previous findings .…”
Section: Discussionsupporting
confidence: 88%
“…Prior work aiming to localize the most prominent degenerative change in svPPA has produced a variety of results, including the anterior fusiform or inferior temporal gyrus , temporal pole (Mummery et al, 2000;Galton et al, 2001;Davies et al, 2009;Rohrer et al, 2009), entorhinal cortex (Chan et al, 2001), and perirhinal cortex (La Joie et al, 2014). This variability likely reflects differences in the neuroimaging analysis technique used and biological variability between patient samples.…”
Section: Reliability Of Focal Atrophy In Svppamentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnosis of PNFA was made based on modified Neary criteria with patients having a speech production impairment characterised by apraxia of speech and agrammatism. Some of these subjects' data have been used in previous studies (Rohrer et al, 2009;Lehmann et al, 2010b,a). All subjects had volumetric MRI acquired on four different 1.5T GE Signa scanners (General Electric, Milwaukee, WI).…”
Section: Cohortmentioning
confidence: 99%
“…The thickness of the cortex is of interest as it develops, follows the normal ageing process and changes under a wide variety of neurodegenerative diseases. Recently, imaging studies of cortical thickness have compared the group-wise differences between healthy control subjects and patients with conditions such as sporadic and familial Alzheimer's disease (AD) Gutierrez-Galve et al, 2009;Knight et al, 2009), fronto-temporal lobar degeneration (FTLD) (Du et al, 2007;Rohrer et al, 2009), posterior cortical atrophy , multiple sclerosis (Sailer et al, 2003), Huntington's disease (Rosas et al, 2008), and the changes that occur in healthy controls under normal ageing (Salat et al, 2004).…”
Section: Introductionmentioning
confidence: 99%